(untitled) (Communication & Society, 2014)
The present article analyses the development of the paid content published on the homepage of The Wall Street Journal’s digital version (from 2010 to 2012) as well as the influence that the variables of type of subject matter, the section in which the content appear and the territorial scope have on the probability of certain contents being paid for. The authors of this article established that the WSJ.com strategy has been evolving from an open paywall model to a much more restrictive one. They also came to the conclusion that payment is closely linked to dissimilar and more specialized content with higher added value that is not easily imitated by the competition.